THE DIGITAL TOOLS FOR LANGUAGE LEARNING (Ustozlar uchun, 2026)
In the modern digital era, language learning has become more accessible and efficient due to the development of technology. This article explores the role of digital tools in learning foreign languages, highlighting the importance of mobile applications such as Duolingo and Babbel, as well as communication platforms like HelloTalk and italki. It also discusses the benefits of multimedia resources, including YouTube, and artificial intelligence tools such as ChatGPT. The article emphasizes that digital tools enhance flexibility, engagement, and accessibility in language learning, while also requiring learner autonomy and consistent practice. Overall, digital technologies have significantly transformed traditional approaches to language education.